Rekonstruksi Nilai Tudang Sipulung Untuk Pencegahan Bullying Dalam Mewujudkan Sekolah Smart - Handy Ferdiansyah; Jamaluddin Ahmad; Usman M; Armayani Armayani; Devy Febrianti; Sunandar Said; Ahmad Mustanir; Afrilia Cahyani; Suleha Suleha; Andi Nilwana; M. Nurzin R Kasau; Eka Eman Rosi (Universitas Pahlawan Tuanku Tambusai, 2026)
The phenomenon of bullying in elementary schools increasingly threatens the learning environment and hinders early childhood character development. This Community Service (PKM) program aims to implement a bullying prevention model based on Bugis local wisdom, specifically the 'Tudang Sipulung' Focus Group Discussion to support the realization of SMART Schools (Maju, Aman, Ramah, dan Tangguh). The activity was conducted at SD Negeri 5 and SD Negeri 7 Watang Sidenreng, involving 60 participants including school principals, teachers, school committee members, and student representatives. The PKM methodology utilized Community Education, Training, and Advocacy approaches structured through socialization, workshops, and the 'Tudang Sipulung' dialogue forum. Program evaluation was conducted using pre- and post-tests to measure participant understanding and assess the establishment of a child-friendly school integrity pact. The results demonstrated a 34.1% increase in participants' understanding of bullying prevention, the establishment of 'Duta SMART' (Polite, Humanizing, Adaptive, Friendly, and Resilient) as peer educators, and the signing of the SMART School Integrity Pact. The integration of Tudang Sipulung values ​​(sipakatau, sipakalebbi, and sipakainge) through direct interaction has proven effective in creating a safe, inclusive, and conducive elementary school environment that supports character education.